2020
DOI: 10.1186/s13020-020-00313-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive QSAR model confirms flavonoids in Chinese medicine can activate voltage-gated calcium (CaV) channel in osteogenesis

Abstract: Background: Flavonoids in Chinese Medicine have been proven in animal studies that could aid in osteogenesis and bone formation. However, there is no consented mechanism for how these phytochemicals action on the bone-forming osteoblasts, and henceforth the prediction model of chemical screening for this specific biochemical function has not been established. The purpose of this study was to develop a novel selection and effective approach of flavonoids on the prediction of bone-forming ability via osteoblasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As one kind of flavonoids in Traditional Chinese medicine, the influence of scutellarein on intracellular calcium has been already studied. For example, it was shown that scutellarein has a mild effect on the intracellular calcium of platelets in a dose‐dependent manner (Tian et al, 2016), and Chan et al demonstrated that scutellarein has high activating effects on CaV channel for osteogenesis (Chan et al, 2020). Here, in our study, it was proved that scutellarein treatment could significantly enhance the [Ca 2+ ] i of non‐capacitated sperm (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…As one kind of flavonoids in Traditional Chinese medicine, the influence of scutellarein on intracellular calcium has been already studied. For example, it was shown that scutellarein has a mild effect on the intracellular calcium of platelets in a dose‐dependent manner (Tian et al, 2016), and Chan et al demonstrated that scutellarein has high activating effects on CaV channel for osteogenesis (Chan et al, 2020). Here, in our study, it was proved that scutellarein treatment could significantly enhance the [Ca 2+ ] i of non‐capacitated sperm (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…QSAR modeling was performed to calculate the mathematical correlations between the chemical properties of QR2 inhibitor compounds, from different bioassays, and their biochemical response on QR2 activity. The biochemical response of the drugs was defined as a function of the chemical properties of the bioassayed compounds [29].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies on flavonoids have shown their notable effect on bone cells, such as increasing osteoblast activity, suppressing osteoclast activity, and protecting against bone loss, in addition to decreasing calcium and phosphate urinary excretion [ 18 ]. Some in vivo studies proved that flavonoids, such as Daidzein, Quercetin, Kaempferol, and Genistein, could affect osteogenesis and bone formation, while some studies report inhibiting effect on osteoclastogenesis and bone resorption [ 19 , 20 ]. Some of the flavonoids, such as isoflavones, accelerate bone formation by inducing osteoblasts differentiation and cell proliferation along with the inhibition of adipogenesis through the nitric oxide and estrogen receptor pathways [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%